2014
DOI: 10.1186/bf03352216
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Equatorial Electrojet determined from an array of magnetometers in N-NE Brazil

Abstract: An array of 29 vector magnetometers was operated in N-NE Brazil from November 1990 until March 1991. We present the analysis of 16 selected quiet days, for which a simple model of an equivalent current distribution for the Sq and EEJ, fits the observed maximum amplitude of the daily variation at midday.In equatorial regions the precise latitude profile of the Sq field is masked by the EEJ. This uncertainty is resolved by assuming that the EEJ, obtained after subtracting the Sq from the daily ranges, should pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…Figure 3 is drawn after Fig. 5 of Rigoti et al (1999). The diagram also shows the EEJ and Sq variations as obtained by Rigoti et al (1999) from the modeling based on all available data for the longitude zone.…”
Section: Direction Of H East Of Geographic Northmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 3 is drawn after Fig. 5 of Rigoti et al (1999). The diagram also shows the EEJ and Sq variations as obtained by Rigoti et al (1999) from the modeling based on all available data for the longitude zone.…”
Section: Direction Of H East Of Geographic Northmentioning
confidence: 99%
“…The average induced effect as measured from the ratio of internal to external component ( H i/ H e) for Sq variations was found to be 0.38. Rigoti et al (1999) estimated that the internal part of H observed in Eastern Brazil region was less than 10% of the external component. These differences may be due to the presence of large conducting region in eastern part of Ethiopia.…”
Section: Effect Of Induced Current Due To Eejmentioning
confidence: 99%
See 3 more Smart Citations